Computational speed-up with a single qudit - Gedik, Zafer; Silva, Isabela Almeida; Çakmak, Baris; Karpat, Göktug [UNESP]; Vidoto, Edson Luiz Géa; Soares-Pinto, Diogo de Oliveira; Azevedo, Eduardo Ribeiro de; Fanchini, Felipe Fernandes [UNESP] (Springer Nature, 2015)
Quantum algorithms are known for providing more efficient solutions to certain computational tasks than any corresponding classical algorithm. Here we show that a single qudit is sufficient to implement an oracle based quantum algorithm, which can solve a black-box problem faster than any classical algorithm. For 2d permutation functions defined on a set of d elements, deciding whether a given permutation is even or odd, requires evaluation of the function for at least two elements. We demonstrate that a quantum circuit with a single qudit can determine the parity of the permutation with only one evaluation of the function. Our algorithm provides an example for quantum computation without entanglement since it makes use of the pure state of a qudit. We also present an experimental realization of the proposed quantum algorithm with a quadrupolar nuclear magnetic resonance using a single four-level quantum system, i.e., a ququart.